An edge-based active contour model using an inflation/deflation force with a damping coefficient. (February 2016) - Ciecholewski, Marcin
Highlights: A much easier initialisation of the contour than in the basic model. Automatically removing self-crossings and loops of the active contour. Automatically dampening the inflation/deflation force of the moving nodes. Automatically adding new nodes and removing superfluous ones. Abstract: This publication presents an edge-based active contour model using the inflation/deflation force, allowing active contour nodes to be moved to find object boundaries in a digital image. The methods proposed in this study make it possible to keep a high value of the inflation/deflation force for each node until the node approaches the boundary of the analysed shape. After the boundary searched for is reached, the value of the inflation/deflation force for these nodes is automatically damped. The solutions used in this paper are of major practical significance if the analysed images contain weak boundaries and/or strong noise at the same time, and on top of that there are strictures of the shape which should be approximated. Experiments were carried out for artificial images as well as USG and MRI medical images, and have confirmed the suitability of the solutions used.